Clinical and pathological features of Merkel cell carcinoma: A 4-year follow-up observational retrospective study in Spain. (February 2022) - Ríos-Martín, Juan José; Rodriguez-Salas, Nuria; Vázquez-Doval, Francisco Javier; Llombart, Beatriz; Rojas-Ferrer, Nohelia; González-Vela, M. Carmen; Zulueta, Teresa; Monteagudo, Carlos; Aneiros-Fernández, José; Beato, María José; Carrillo, Rosario; Silva-Carmona, Mary Yohana; et al.
Abstract: Background: Merkel cell carcinoma (MCC) is a malignant skin cancer with a 5-year survival rate of approximately 50%. Knowledge of MCC has increased in recent years mostly due to improved diagnosis techniques. In Spain there is lack of information regarding the incidence and tumour characteristics, and the treatment approaches are not standardised. The objective of this study was to provide information of the clinical and epidemiological characteristics of MCC patients in Spain. Methods: Retrospective, observational study involving 192 patients from 25 Spanish hospitals. Evaluated variables included overall survival and incidence rate of Merkel cell polyomavirus, in patients diagnosed from 2012 to 2016. Results: The Spanish incidence rate was estimated 0.32/100, 000 inhabitants/year, with variations according to geographical regions, being slightly higher in areas with greater sunlight exposure. In total, 61.5% of tumours showed expansive growth (progressive growth of the tumour), 78.6% showed localisation in UV-exposed skin. 97.4% of patients were diagnosed by excisional biopsy. Surgery was the first line treatment in 96.6% of patients, radiotherapy in 24.6%, and chemotherapy in 6.3%. These treatments were not mutually exclusive. Median overall survival was 38.3 months (78.4% at 12 months and 60% at 24 months). MCPyV was present in 33.8% of patients. Conclusion: The incidence of MCC in Spain is one of the highest in Europe, with a slight predominance in men. The sample has shown that a biopsy is available for diagnosis in most cases. Moreover, the treatment is surgical when the tumour is localized and is associated with lymphadenectomy, and/or it is radiotherapy if widespread. Highlights: The incidence of Merkel cell carcinoma in Spain is one of the highest in Europe. Spanish incidence rate of Merkel cell carcinoma: 0.32/100, 000 inhabitants/year. Surgery was the first line treatment in 96.6% of the patients. MCPyV incidence is in accordance to expected values regarding solar exposition.